2003
DOI: 10.1086/374398
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Use of Residential Mailing Addresses in a Metropolitan Household Survey

Abstract: We developed a sampling frame for a probability-based household survey by purchasing an exhaustive list of over 818,000 residential mailing addresses in Dallas County, Texas. The addresses were obtained from the Delivery Sequence File (DSF) offered by the US Postal Service (USPS) through a nonexclusive license agreement with private companies. The DSF is a computerized file that contains all delivery point addresses serviced by the USPS, with the exception of general delivery. We used the geographic coordinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 3 publications
2
35
0
Order By: Relevance
“…Early uses of the United States Postal Service (USPS) Delivery Sequence File (DSF) were focused on the search for more cost-effective approaches to on-site enumeration for in-person surveys (e.g., Iannacchione et al 2003). Survey scientists at RTI (Iannacchione and colleagues) and at NORC conducted several extensive comparisons of address-based samples and household unit (HU) field enumeration (see O'€™Muircheartaigh et al 2002;O'Muircheartaigh et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Early uses of the United States Postal Service (USPS) Delivery Sequence File (DSF) were focused on the search for more cost-effective approaches to on-site enumeration for in-person surveys (e.g., Iannacchione et al 2003). Survey scientists at RTI (Iannacchione and colleagues) and at NORC conducted several extensive comparisons of address-based samples and household unit (HU) field enumeration (see O'€™Muircheartaigh et al 2002;O'Muircheartaigh et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have suggested that ABS is more cost-effective than RDD, provides greater coverage of residential homes and produces higher response rates for research studies 23 24. Selected commercial companies have access to the US Postal Service's Delivery Sequence File, all addresses to which mail is delivered.…”
Section: Methodsmentioning
confidence: 99%
“…The concept of using the CDSF to generate a sampling frame was first examined by Iannacchione, Staab, and Redden (2003). Address-based sampling emerged as an alternative to manual enumeration to enfranchise individuals without landline phones, historically reached through random-digit dial (RDD) surveys.…”
Section: Rationale For Address-based Sampling Methodsmentioning
confidence: 99%